Da festa ao cerimonial midiático: as estratégias de midiatização da teleromaria da Medianeira pela Rede Vida - Borelli, Viviane (Universidade do Vale do Rio do Sinos, 2007)
This research proposes to examine the manners with that processes by media affects the rituals and the religious practices through analysis of the strategies developed by Rede Vida Network in the construction of “Tele Romaria of Medianeira”, that takes place in Santa Maria, Rio Grande do Sul, Brazil. It is shown that passes to impose own rules and grammars when producing the event, the media televise, generating another ceremony, the strategies of media. When analyzing these process - of the event to television ceremonial from, identify different moments and stages of affectation of the ceremonial by media on the religious practices, evidencing as the mediatization structures and it regulates the relationships among the areas by the work of symbolic devices itselves. In these conditions the thesis shows that the process of mediatization of the Romaria ends generating the Romaria by media product. In this context, the investigation is elaborated in a perspective in that, more and more, the parties become co-de
Keywords: igreja católica; massa; midiatização; programa; Rede Vida; religião; romaria da Medianeira; televisão; mídia; device; Rede Vida Network; religion; Romaria; mediatization; Ciências Sociais Aplicadas